Preparation of mono-substituted malonic acid half oxyesters (SMAHOs) - Xavier, Tania; Condon, Sylvie; Pichon, Christophe; Le Gall, Erwan; Presset, Marc (Beilstein Journal of Organic Chemistry, 2021)
The use of mono-substituted malonic acid half oxyesters (SMAHOs) has been hampered by the sporadic references describing their preparation. An evaluation of different approaches has been achieved, allowing to define the best strategies to introduce diversity on both the malonic position and the ester function. A classical alkylation step of a malonate by an alkyl halide followed by a monosaponification gave access to reagents bearing different substituents at the malonic position, including functionalized derivatives. On the other hand, the development of a monoesterification step of a substituted malonic acid derivative proved to be the best entry for diversity at the ester function, rather than the use of an intermediate Meldrum acid. Both these transformations are characterized by their simplicity and efficiency, allowing a straightforward access to SMAHOs from cheap starting materials.
Keywords: alkylation; esterification; malonate; saponification; SMAHO